2020
DOI: 10.1155/2020/3109069
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation Effect of Patchouli Alcohol in Rat Corpus Cavernous and Its Underlying Mechanisms

Abstract: In this study, we investigated the relaxation effect and mechanisms of patchouli alcohol (PA) on rat corpus cavernosum. Corpus cavernosum strips were used in organ baths for isometric tension studies. The results showed that PA demonstrated concentration-dependent relaxation effect on rat corpus cavernosum. The relaxant response to PA was not influenced by tetrodotoxin and atropine while it was significantly inhibited by removal of endothelium. L-NG-nitroarginine methyl ester (L-NAME, a nitric oxide synthase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Additionally, when the tissue was pre-incubated for 20 min with the essential oil, the dose–response curves in response to KCl were significantly reduced. The action of VPEO can be attributed to its major component, patchouli alcohol (20.8%), a tricyclic sesquiterpene that has displayed similar results in other types of smooth muscle, such as the aorta [ 58 ] and rat corpus cavernosum [ 59 ]. However, the synergistic effects of other VPEO components, such as α-patchoulene (5.8%), α-humulene (6.1%), and seychellene (7.6%), at lower concentrations cannot be rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when the tissue was pre-incubated for 20 min with the essential oil, the dose–response curves in response to KCl were significantly reduced. The action of VPEO can be attributed to its major component, patchouli alcohol (20.8%), a tricyclic sesquiterpene that has displayed similar results in other types of smooth muscle, such as the aorta [ 58 ] and rat corpus cavernosum [ 59 ]. However, the synergistic effects of other VPEO components, such as α-patchoulene (5.8%), α-humulene (6.1%), and seychellene (7.6%), at lower concentrations cannot be rejected.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cholinergic stimulation of the cavernous nerve leads to increased blood flow within the penis, on the contrary the adrenergic stimulation reduces blood flow leading to the flaccid state [ 31 ], according to our results, a relaxation was observed with sildenafil whilst SEAF and LEAF did not reveal any effect on adrenergic receptors. On the other hand, the exposition to CaCl 2 leads to extracellular calcium influx after the opening of calcium channels [ 32 ]. Although, non-significant differences were observed in LEAF and SEAF, at 0.1 mg/mL antagonized the Ca 2+ -induced contractions in rat’s penile tissue.…”
Section: Discussionmentioning
confidence: 99%
“…After mixing, the sample was incubated in the dark for 30 min and the absorbance was read at 515 nm using a Genesys 150 spectrophotometer (Thermo Scientific, Waltham, MA, USA). The standard curve was elaborated with Trolox at concentrations of 0 to 800 μmol/mL [ 32 ]. The Trolox equivalent antioxidant capacity (TEAC) was expressed as μmol Trolox equivalent per gram of extract (µmol TE/g of extract).…”
Section: Methodsmentioning
confidence: 99%
“…Olfactory perception is well known to have strong connections with the amygdala and activates brain areas that regulate emotions, such as the orbitofrontal cortex, hippocampus, and amygdala (Kadohisa, 2013;Wilson & Stevenson, 2003). Willander and Larsson (2006) demonstrated that memories induced by olfactory stimulation were associated with stronger feelings compared to other visual and auditory systems including relaxant effects and impacts on mood (Chen et al, 2020;Genc & Saritas, 2020;Krusemark et al, 2013). Recent research shows that the existence of pleasant fragrances resulted in improved creativity (Baron & Thomley, 1994;Ehrlichman & Bastone, 1992), and that olfactory cues helped participants better perceive emotions (Xiang et al, 2016).…”
Section: Fragrance and Creative Self-expressionmentioning
confidence: 99%